2023
DOI: 10.11604/pamj.2023.44.163.27841
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with malnutrition among school adolescents of Durame Town, Kambeta Tembaro Zone, Ethiopia

Abstract: Introduction malnutrition is a major public health issue affecting adolescents globally and developing countries in particular. Adolescent period is very sensitive to malnutrition. Adolescent malnutrition can be affected by different factors. The objective of this study was to assess prevalence and associated factors of adolescent malnutrition among high school students. Methods an institutional-based cross-sectional study was carried out among school adolescents in Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Moreover, our results revealed a lower prevalence of stunting compared with the pooled prevalence of stunting reported in a meta-analysis among adolescents in South Africa (9·6%) [ 6 ] and Ethiopia (22.4%) [ 7 ]. On the other hand, the prevalence (7.5%) of stunting in our study was higher than that recently reported (5.7%) among school adolescents in high schools in the town of Durame in Ethiopia [ 11 ]. Although none of the investigated factors (age, sex, parents’ education, and occupation) were associated with stunting in our study, several previous studies in Africa have shown that increasing age [ 20 , 21 ], male sex [ 7 , 15 ], and female sex [ 17 ] were associated with stunting.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Moreover, our results revealed a lower prevalence of stunting compared with the pooled prevalence of stunting reported in a meta-analysis among adolescents in South Africa (9·6%) [ 6 ] and Ethiopia (22.4%) [ 7 ]. On the other hand, the prevalence (7.5%) of stunting in our study was higher than that recently reported (5.7%) among school adolescents in high schools in the town of Durame in Ethiopia [ 11 ]. Although none of the investigated factors (age, sex, parents’ education, and occupation) were associated with stunting in our study, several previous studies in Africa have shown that increasing age [ 20 , 21 ], male sex [ 7 , 15 ], and female sex [ 17 ] were associated with stunting.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results were slightly lower than the prevalence of overweight and obesity reported in sub-Saharan Africa. For example, of the 498 adolescents in Ethiopia, 9.2% were overweight [ 11 ], and in the Bauchi metropolis, Nigeria, 11.0% and 9.7% of the adolescents were overweight and obese, respectively [ 22 ]. Moreover, at Rivers State University in Nigeria, 19.9% of 10–17-year-old adolescents were overweight/obese [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations